The threat of midge‐borne equine disease: investigation of Culicoides species on UK equine premises. (22nd March 2014) - Robin, M.; Archer, D.; Garros, C.; Gardès, L.; Baylis, M.
Abstract : There are concerns that outbreaks of exotic or novel vector‐borne viral diseases will increasingly occur within northern Europe and the UK in the future. African horse sickness (AHS) is a viral disease of equids that is transmitted by Culicoides and is associated with up to 95 per cent mortality. AHS has never occurred in the UK; however, it has been suggested that appropriate Culicoides species and climatic conditions are present in northern Europe to support an outbreak. No data are currently available regarding the Culicoides species present on UK equine properties. This study demonstrates the presence of potential AHS virus vector Culicoides species on both urban and rural equine properties within the south‐east UK. PCR analysis revealed that engorged members of these species contained equine DNA, proving a direct vector–host interaction. It is therefore possible that an AHS outbreak could occur in the UK if the virus were to be imported and, given the severe welfare and economic consequences of AHS, this would have devastating consequences to the naïve UK equine population.